Organosilicone double-long-chain diquaternary ammonium salt acts as a biofilm scavenger to ameliorate colitis induced by dextran sulfate sodium salt - Shi, Shaopei; Tang, Guoxing; Wei, Juan; Shen, Si; Ding, Zhihao; An, Qin; Tao, Hui; Wang, Fangyu (Frontiers in Immunology, 2025)
ObjectiveThe treatment of ulcerative colitis (UC) remains challenging due to limited efficacy and significant side effects. Organosilicone Double-Long-Chain Diquaternary Ammonium Salt (JUC Spray Dressing) exhibits antibacterial, anti-inflammatory, and wound-healing properties. This study aimed to evaluate the therapeutic effects of JUC Spray Dressing in a Dextran Sulfate Sodium Salt (DSS)-induced UC mouse model and explore its potential mechanisms of action.MethodsA UC model was induced in mice using 3% DSS, followed by JUC Spray Dressing enema treatment. Disease activity index (DAI), histological scores, bacterial biofilms on the intestinal mucosa, and tight junction integrity were assessed. Inflammatory cytokine levels in peripheral blood were measured, and 16S rDNA amplicon sequencing was performed to analyze cecal microbiota composition.ResultsJUC Spray Dressing significantly alleviated UC symptoms and reduced colonic congestion, with no significant difference compared to other treatment groups (P > 0.05). All treatments significantly decreased the expression of inflammatory cytokines in peripheral blood (P < 0.0001), with no significant differences among the groups. Additionally, all treatments effectively reduced biofilm thickness and bacterial abundance, improving intestinal barrier integrity. JUC Spray Dressing inhibited harmful bacteria such as Bacteroides spp. without significantly altering overall microbial composition.ConclusionsJUC Spray Dressing effectively removes intestinal bacterial biofilms, reduces inflammation, and enhances barrier function to alleviate UC symptoms. Its efficacy appeared comparable to conventional treatments, suggesting potential as an alternative therapeutic option; however, the present study did not assess mucosal safety, and dedicated toxicology studies are required to establish safety for intraluminal use.